Ecotourism as a Driver for Sustainable Waste Management and Environmental Conservation in Lhokseumawe, Indonesia - Rahman, Bobby; Teuku Muzaffarsyah; Teuku Zulkarnaen; Al Fahmi, M. Lutfi; Meliza, Richa (Samarah: Jurnal Hukum Keluarga dan Hukum Islam, 2026)
This study evaluates the role of ecotourism as a strategy for promoting sustainable waste management in environmentally friendly tourist destinations in Lhokseumawe City, Aceh. Research using qualitative methods was conducted with a case study approach in several tourist destinations that have implemented ecotourism concepts, such as community-based waste management and the use of environmentally friendly technology. Data were collected through in-depth interviews, observations, and a literature review, complemented by questionnaires administered to explore the perceptions of tourists, local communities, and business actors regarding the effectiveness of, and support for, sustainable waste management policies. The findings indicate that the implementation of ecotourism has not yet played a significant role in improving waste management effectiveness in tourist areas. Ecotourism principles have not been comprehensively applied; as a result, destinations have not succeeded in maintaining environmental cleanliness, attracting sustainability-conscious visitors, or fostering synergy between local communities and the government. Although tourists and local residents generally responded positively to these initiatives and expressed support for ecotourism-based waste management policies, many still perceive waste management as primarily the responsibility of the government. This study contributes to the literature on sustainable waste management and may serve as a reference for policymakers and tourism practitioners seeking to enhance environmental quality through an ecotourism approach.